1999
DOI: 10.1111/j.1469-7793.1999.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of guinea‐pig vagal airway afferent neurones to mechanical stimulation

Abstract: The sensory nerve fibres supplying the guinea-pig trachea and main-stem bronchi are mainly vagal fibres with somata located within the nodose and jugular ganglia (Kummer et al. 1992;Riccio et al. 1996b). While subpopulations of these nerve endings can be excited by chemical and non-isoosmotic stimuli, the majority of them respond to mechanical stimuli (Riccio et al. 1996a;Pedersen et al. 1998). Of the fibres that respond to a von Frey fibre mechanical stimulus, there are both low threshold and high threshold m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…The terminals are exquisitely sensitive to a punctate mechanical "touch" stimulus applied to the mucosa. The nerves respond primarily to the dynamic phase of a rampand-hold mechanical stimulus applied to the mucosa, thus resembling a rapidly adapting response (7). Unlike RAR nerves, however, these fibers are relatively insensitive to smooth muscle constriction or stretch (longitudinal or circumferential).…”
Section: Nociceptorsmentioning
confidence: 99%
“…The terminals are exquisitely sensitive to a punctate mechanical "touch" stimulus applied to the mucosa. The nerves respond primarily to the dynamic phase of a rampand-hold mechanical stimulus applied to the mucosa, thus resembling a rapidly adapting response (7). Unlike RAR nerves, however, these fibers are relatively insensitive to smooth muscle constriction or stretch (longitudinal or circumferential).…”
Section: Nociceptorsmentioning
confidence: 99%
“…On the other hand, the afferents involved in cough are located in the tracheal bifurcation and are also thought to have their cell bodies in the nodose ganglion although in the guinea pig these are contained in the jugular ganglion (McAlexander et al, 1999). The dorsal swallowing center in the nucleus tractus solitarius contains central patterning for swallowing with input to the laryngeal motor neurons via the solitari-ambiguus pathway (Jean, 2001).…”
Section: Sensori-motor Reflexes Affecting Laryngeal Muscle Controlmentioning
confidence: 99%
“…Earlier research has shown that the adaptation response which underlies these two vagal populations in the lungs highly correlates with embryological origin (nodose versus jugular) (McAlexander et al, 1999). Afferent fibers from the placode-derived nodose ganglion, predominately rapidly adapt, whereas the majority of fibers that originate from the neural crest-derived jugular ganglion adapt slowly (McAlexander et al, 1999). It is noted that the adaptation response initiated at terminal endings does not always equate with the same electrophysiological response present at the soma (McAlexander et al, 1999).…”
Section: Electrophysiological Properties Of Ng Neuronsmentioning
confidence: 98%
“…For instance, mechanosensitive vagal afferents innervating the lungs have been shown to fall into either slowly adapting receptors (a burst of APs which are maintained as long as the stimulus is present) or rapidly adapting receptors (a brief burst of APs, after which, they rapidly adapt and may cease firing) (Knowlton andLarrabee, 1946, Widdicombe, 1954). Earlier research has shown that the adaptation response which underlies these two vagal populations in the lungs highly correlates with embryological origin (nodose versus jugular) (McAlexander et al, 1999). Afferent fibers from the placode-derived nodose ganglion, predominately rapidly adapt, whereas the majority of fibers that originate from the neural crest-derived jugular ganglion adapt slowly (McAlexander et al, 1999).…”
Section: Electrophysiological Properties Of Ng Neuronsmentioning
confidence: 99%
See 1 more Smart Citation